The Relevance of Words and Meaning in Students’ Infographics Based on Sperber & Wilson - Andayani, Wuwuh; Zainal Rafli; Fathiaty Murtadho (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The use of relevant and concise wording in infographics is crucial to ensure that the information presented can be quickly and effectively understood by readers. However, existing infographics still need to strike a balance between information density and clarity of delivery. This study explores the relevance of words and meaning in student-created infographics, using Sperber & Wilson’s Relevance Theory (1986, 1995) as a framework. By analyzing three student-created infographics, the study identified the main structural elements of infographics: description (general overview), details (specific information), and significance (practical value). It also examined audience intentions, categorized as either informative or communicative. The results revealed that the "significance" element dominated all the infographics, underscoring the importance of the practical value and relevance of the information presented. Audiences were more likely to engage with infographics they found informative, although a balance between informative and communicative aspects—such as seen in Infographic 1—yielded optimal impact on audience comprehension and engagement. This study highlighted the importance of infographic design that emphasized word and meaning relevance to create effective communication. Recommendations are provided for more strategically integrating communicative elements to enhance the appeal and effectiveness of infographics in various communication contexts. Keywords: Relevance, Infographics, Relevance Theory, Visual Writing, Audience Understanding.